The essential Rumi - Ǧalāl-ad-Dīn Rūmī 1207-1273 (HarperOne, 2004)
A comprehensive collection of ecstatic poetry that delights with its energy and passion, The Essential Rumi brings the vibrant, living words of famed thirteenth-century Sufi mystic Jelalludin Rumi to contemporary readers
Originally published in 1995
Includes bibliographical references (pages 371-378) and index
Keywords: Ǧalāl-ad-Dīn Rūmī -- 1207-1273; Übersetzung; Lyrik; Englisch; Jalāl al-Dīn Rūmī / Maulana / 1207-1273 / Translations into English; Sufi poetry, Persian / Translations into English